2013
DOI: 10.1002/ijc.28418
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic immunization and local low‐dose tumor irradiation, a reinforcing combination

Abstract: Therapeutic cancer vaccines show promise in preclinical studies, yet their clinical efficacy is limited. Increased recruitment of immune cells into tumors and suppression of the immune suppressive tumor environment are critical components toward effective cancer immunotherapies. Here, we report how local low-dose irradiation, alone or with a therapeutic immunization based on Semliki Forest virus (SFV) against human papillomavirus (HPV)-related cancer, influences these immune mechanisms. We first demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
(78 reference statements)
0
44
1
Order By: Relevance
“…30,31 Recently, low-dose radiotherapy has been reported to safely control gastric cancer-related symptoms, demonstrating significant clinical utility. 29 Previous studies have demonstrated that local low-dose irradiation (LDI) alone resulted in an increase in intratumoral CD8+ T cells, 32 which was shown to be correlated with the upregulated expression of adhesion molecules on tumor vasculature and the increased expression of chemoattractants. 33 Furthermore, local LDI could promote the normalization of aberrant vasculature, which facilitated the entry of T lymphocytes into tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Recently, low-dose radiotherapy has been reported to safely control gastric cancer-related symptoms, demonstrating significant clinical utility. 29 Previous studies have demonstrated that local low-dose irradiation (LDI) alone resulted in an increase in intratumoral CD8+ T cells, 32 which was shown to be correlated with the upregulated expression of adhesion molecules on tumor vasculature and the increased expression of chemoattractants. 33 Furthermore, local LDI could promote the normalization of aberrant vasculature, which facilitated the entry of T lymphocytes into tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also identified that local LDI induces recruitment of tumor-specific T lymphocytes to the tumor site, but focused only on the cell behavior. 32,34,46 Therefore, this is the first study to use local irradiation, which is one of the most commonly used treatment modalities for gastric cancer, as a chemoattractant for a hCTL membrane-based drug delivery system.…”
mentioning
confidence: 99%
“…7 This difference may be accounted for by differences IL-2 receptor levels expressed on activated T cells and by IL-2 receptor expression on other infiltrating lymphocytes, such as natural killer cells. The synergistic increase in tracer accumulation was also observed in immunerelated organs.…”
Section: Discussionmentioning
confidence: 99%
“…Our viral vector is based on recombinant Semliki Forest virus (rSFV) encoding a fusion protein of E6 and E7 derived from human papilloma virus (HPV) type 16 (rSFVeE6,7). 6 In combination with local irradiation, immunization with rSFVeE6,7 in tumor-bearing mice demonstrated a synergistic antitumor effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation